2000
DOI: 10.1530/eje.0.1430741
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of antithyroid autoantibodies in pregnant women at increased risk of gestational diabetes mellitus

Abstract: Background: Thyroid autoantibodies (ThyAb) and subclinical hypothyroidism occur more frequently in pregnant women with insulin-dependent diabetes mellitus than in healthy pregnant women. Few studies have investigated the presence of ThyAb in women with gestational diabetes mellitus (GDM), and no significant association between diabetes in pregnancy and thyroid function has been reported. Objective: To assess the thyroid biochemical profile and estimate the prevalence of ThyAb in a group of pregnant women at in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 43 publications
(40 reference statements)
0
45
1
3
Order By: Relevance
“…The same authors suggested that if adequate control of the maternal diabetic condition is achieved, the alterations in foetal thyroid hormone economy would be avoided. Moreover, in a previous study (30), we reported an increased risk of subclinical hypothyroidism during pregnancy in a group of women with gestational diabetes. Taken together, all these findings highlight the importance of an adequate metabolic control during pregnancy in order to reduce maternal and foetal morbidity, including transient and permanent forms of neonatal hypothyroidism.…”
Section: Discussionmentioning
confidence: 69%
“…The same authors suggested that if adequate control of the maternal diabetic condition is achieved, the alterations in foetal thyroid hormone economy would be avoided. Moreover, in a previous study (30), we reported an increased risk of subclinical hypothyroidism during pregnancy in a group of women with gestational diabetes. Taken together, all these findings highlight the importance of an adequate metabolic control during pregnancy in order to reduce maternal and foetal morbidity, including transient and permanent forms of neonatal hypothyroidism.…”
Section: Discussionmentioning
confidence: 69%
“…Another hypothesized connection between diabetes and depression in the perinatal period is thyroid function. In one study, pregnant women who developed GDM had a mean free thyroxine concentration (measured ∼ 28 weeks) significantly lower than that observed in healthy pregnant women [22]. Another study found antenatal measurements of total thyroxine and free thyroxine to be negatively and significantly correlated with mean depression scores at three postpartum periods [23].…”
Section: Hypothesized Mechanisms Underlying the Association Between Dmentioning
confidence: 94%
“…Feely et al documented that SCH coexisted in 30% cases of GDM 55 . Many other literatures have also documented an association of thyroid abnormalities, notably overt and subclinical hypothyroidism as well as autoimmune thyroiditis with GDM [56][57][58][59][60] . This correlation has been substantiated by depiction of an inverse association between Metforfin and TSH level 61,62,63 .…”
Section: Discussionmentioning
confidence: 92%